Understanding of Islamic Studies Through Sharia Economics Perspective in Indonesia - Hendri Hermawan Adinugraha; Ali Muhtarom (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2021)
The existence of religions now required to be actively involved in solving the problems facing by mankind. One of the problems faced is the interaction with the modern economy. One of the approaches that can be developed for discussion of Islamic studies is Sharia Economics perspective. This research aims to describe the implementation of Sharia Economics perspective in order to understand Islamic studies. Research methods in this research use literature research from both national and international journals and books related to the topic. Ideally, the Sharia Economics approach should be integrative and interdisciplinary. Integrative method seeks to combine the revelation and ra’y in economic studies to understand Islam from the economic aspect. While the method of interdisciplinary attempt to approach it with a wide range of disciplines such as economics, politics, law, history, so that produce a comprehensive study and relevant to the happening facts/phenomena.